Urothelial Bladder Cancer: An Update on Molecular Pathology with Clinical Implications - Bertz, Simone; Eckstein, Markus; Stoehr, Robert; Weyerer, Veronika; Hartmann, Arndt (European Urology Supplements, 2017)
Urothelial bladder cancer is a heterogenous disease with distinct clinical and histopathological features. In the last few years it became clear that papillary, mostly noninvasive, disease with few molecular changes and aggressive urothelial carcinoma are genomically separate diseases. Recently, several studies found that invasive bladder cancer can also be separated into several molecular subgroups. In the present review we summarize molecular alterations, diagnostic markers, and molecular subgroups in urothelial bladder cancer and discuss their clinical relevance for prognosis, prediction of recurrence and progression, and therapeutic response to chemotherapy, radiotherapy, and immunotherapy. (C) 2017 European Association of Urology. Published by Elsevier B.V. All rights reserved.
EVALuna2:33791